Tuning of the acoustic impedance of a shunted electro-mechanical diaphragm for a broadband sound absorber. (1st July 2019) - Zhang, Yumin; Wang, Chunqi; Huang, Lixi
Highlights: Acoustic reactance of shunted diaphragm can be tuned for broadband absorption. Shunt circuit introduces negative acoustic mass and stiffness. Positive acoustic mass and stiffness of the diaphragm can be canceled in broadband. A design procedure is proposed for uniform sound absorption over a broadband. Experimental results agree with theoretical predictions. Abstract: Recent study shows that a suspended diaphragm may function as an efficient sound absorbing device if a properly designed shunt electrical circuit is connected. The sound absorption performance mostly depends on the acoustic impedance of the suspended diaphragm, which is strongly coupled to the electrical impedance of the shunt circuit via the electromechanical coupling induced by a moving-coil in a DC magnetic field. This study concerns tuning the acoustic impedance of the diaphragm with shunt electrical circuit, or a 'shunted-electromechanical-diaphragm' (SEMD). A lumped parameter model is used to analyze the effect of each circuit element on the acoustic impedance of the SEMD. Results show that sound absorption coefficients of the SEMD can be adjusted at low, middle and high frequencies by tuning the capacitance, resistance and inductance of the circuit, respectively. Further analyses show that the shunt circuit introduces negative acoustic mass and reactance at middle frequencies, which can be used to cancel the acoustic mass and stiffness of the diaphragm, resulting in a vanishing reactance of the diaphragm in a broad frequency band. By tuning the resistance of the circuit to modify the acoustic resistance of the SEMD, the sound absorption coefficient of the SEMD can be adjusted to any specific level. A prototype SEMD is tested with different sets of circuit parameters using an acoustic impedance tube. Agreement is observed between the experimental results and theoretical predictions.